An evolutionarily ancient mechanism for regulation of hemoglobin expression in vertebrate red cells - Miyata, Masato (Blood, 2020)
The oxygen transport function of hemoglobin (HB) is thought to have arisen ∼500 million years ago, roughly coinciding with the divergence between jawless (Agnatha) and jawed (Gnathostomata) vertebrates. Intriguingly, extant HBs of jawless and jawed vertebrates were shown to have evolved twice, and independently, from different ancestral globin proteins. This raises the question of whether erythroid-specific expression of HB also evolved twice independently. In all jawed vertebrates studied to date, one of the HB gene clusters is linked to the widely expressed NPRL3 gene. Here we show that the nprl3-linked hb locus of a jawless vertebrate, the river lamprey (Lampetra fluviatilis), shares a range of structural and functional properties with the equivalent jawed vertebrate HB locus. Functional analysis demonstrates that an erythroid-specific enhancer is located in intron 7 of lamprey nprl3, which corresponds to the NPRL3 intron 7 MCS-R1 enhancer of jawed vertebrates. Collectively, our findings signify the presence of an nprl3-linked multiglobin gene locus, which contains a remote enhancer that drives globin expression in erythroid cells, before the divergence of jawless and jawed vertebrates. Different globin genes from this ancestral cluster evolved in the current NPRL3-linked HB genes in jawless and jawed vertebrates. This provides an explanation of the enigma of how, in different species, globin genes linked to the same adjacent gene could undergo convergent evolution.